Analisis Faktor Pembentuk Keputusan Pemilihan Perguruan Tinggi Swasta Universitas Telkom: Studi Pada Mahasiswa Prodi S1 Administrasi Bisnis Fakultas Komunikasi Dan Bisnis Universitas Telkom Angkatan 2016 - Mahendra Fakhri; Alini Gilang; Nining Ratnayu (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2017)
In Indonesian, public university and private university compete so tightly to create qualified graduates. Beside that, they compete to provide best educational services to get more students. This study aimed to analyze dominant factors that forming student decision in choosing Telkom University study program S1 Business Administration. The type of this study is descriptive research with nonprobability sampling and simple random sampling technique. Questionnaires were distributed to 100 samples of Business Administration’s students’ batch 2016. This research used variable such as: friends attending college, influence of parents, influence of friends, influence of other individuals, location, academic program, academic reputation, educational facilities, costs, available of financial aid, employment opportunities, advertising, HEI’s representative and visit campus. Based on analysis, it was found 5 new factors such as college’s image, college promotion, influence of parents, influence of friends and college’s location. College’s image factor has the biggest variances value such as 29,15% in forming choise decision of Telkom University Prodi S1 Business Administration as a private college.